1981
DOI: 10.1017/s0043174500062068
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption, Desorption, and Mobility of Metolachlor in Soils

Abstract: Metolachlor [2-chloro-N-(2-ethyl-6-methylphenyl)-N-(2-methoxy-1-methylethyl)acetamide] has considerable potential for yellow nutsedge (Cyperus esculentusL.) control in crops commonly produced in the Texas High Plains. Little information is available, however, concerning adsorption characteristics of metolachlor in soils of this region. Adsorption and movement of metolachlor were determined in three commonly occurring soils of the Texas High Plains. Organic carbon contents of the soils by weight varied from 0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
2
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 6 publications
7
38
2
2
Order By: Relevance
“…For metolachlor, Rion > Norfolk . Webster ) Cape Fear, as determined by MI values of 21.9, 17.4, 8.5, and 7.2, respectively, which were inversely related to soil OM (r ) -0.97***), HM (r ) -0.87***), and clay (r ) -0.67*) contents, as also reported in the literature (19,(36)(37)(38)(39), and CEC (r ) -0.85***) and pore volume (r ) -0.84***) ( Figure 5 and Table 1). Metolochlor mobility was also correlated with soil bulk density (r ) 0.86***).…”
Section: Suspension Ph Effects On Sorption/desorption Of Imazaquinsupporting
confidence: 81%
“…For metolachlor, Rion > Norfolk . Webster ) Cape Fear, as determined by MI values of 21.9, 17.4, 8.5, and 7.2, respectively, which were inversely related to soil OM (r ) -0.97***), HM (r ) -0.87***), and clay (r ) -0.67*) contents, as also reported in the literature (19,(36)(37)(38)(39), and CEC (r ) -0.85***) and pore volume (r ) -0.84***) ( Figure 5 and Table 1). Metolochlor mobility was also correlated with soil bulk density (r ) 0.86***).…”
Section: Suspension Ph Effects On Sorption/desorption Of Imazaquinsupporting
confidence: 81%
“…Sorption of metolachlor and/or metolachlor degradates contributed to the dissipation of extractable metolachlor in both the unsaturated surface and the subsurface soil. The organic carbon content of the soil has been found to be the most important soil property influencing the adsorption of metolachlor [30][31][32][33][34][35]. Soil-bound residues increased from 17.2 to 27.6% in unsaturated surface soil and from 3.8 to 8.3% in unsaturated subsurface soil at 60 and 120 d. Greater quantities of soil-bound residues formed in the surface soil relative to the subsurface soil, presumably as a result of the greater quantity of organic carbon in the surface soil.…”
Section: Effect Of Soil Depthmentioning
confidence: 99%
“…Wang et al [4] and Liu et al [5] investigated the behavior of acetanilide herbicides in soil and drew the conclusion that the adsorption of butachlor on soil from water was an important factor affecting its fate in soil, while the adsorption of butachlor on soil is affected by various properties of the soil itself. To understand adsorption as well as the factors affecting it, many scientists have studied the adsorption of butachlor on soil and HAs from water and found that the adsorption capacity is closely related to soil organic matter (SOM) [6][7][8] and the mechanism is mainly the formation of H-bonds [4,5]. However, research about the adsorption of butachlor on different kinds of soils from China and the HAs from the soil samples using FTIR and CP-MAS 13 C NMR was unavailable.…”
Section: Introductionmentioning
confidence: 99%